Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1542/peds.111.5.e555
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy Use in Jaundiced Newborns in a Large Managed Care Organization: Do Clinicians Adhere to the Guideline?

Abstract: ABSTRACT. Objective. In 1994, the American Academy of Pediatrics (AAP) published a practice guideline with age-specific thresholds for phototherapy for healthy term newborns with hyperbilirubinemia. The purpose of this study was to examine adherence to the guideline in a large managed care organization.Methods. We conducted a retrospective cross-sectional analysis of linked computerized databases from 11 Northern California Kaiser Permanente Medical Care Program hospitals. Newborn infants included were at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 28 publications
3
52
0
1
Order By: Relevance
“…5 Significant differences in phototherapy use in different hospitals within the same health care system has been reported previously. 2,6 In a study of 11 Kaiser Permanente hospitals, the single most important predictor of phototherapy use, according to AAP guidelines, was hospital of birth. 6 In this study, infants at the hospital that uses pediatric nurse practitioners received phototherapy less often according to the guideline.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Significant differences in phototherapy use in different hospitals within the same health care system has been reported previously. 2,6 In a study of 11 Kaiser Permanente hospitals, the single most important predictor of phototherapy use, according to AAP guidelines, was hospital of birth. 6 In this study, infants at the hospital that uses pediatric nurse practitioners received phototherapy less often according to the guideline.…”
Section: Discussionmentioning
confidence: 99%
“…2,6 In a study of 11 Kaiser Permanente hospitals, the single most important predictor of phototherapy use, according to AAP guidelines, was hospital of birth. 6 In this study, infants at the hospital that uses pediatric nurse practitioners received phototherapy less often according to the guideline. Although this may be a factor in the interhospital variation in this study, it does not explain the variation in the Kaiser Permanente study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phototherapy is the primary treatment in neonates with unconjugated hyperbilirubinemia.and phototherapy is very safe and may have no serious long-term effects in neonates. 103 Exchange transfusion became the second-line treatment when phototherapy failed to control serum bilirubin levels. However, data have shown that treatment with IVIG in infants with Rh or ABO isoimmunization can significantly reduce the need for exchange transfusions.…”
Section: Neonatal Jaundicementioning
confidence: 99%